Genome wide analyses reveal the role of mutator phenotypes in Mycobacterium tuberculosis drug resistance emergence - R. Zein-Eddine; A. Le Meur; S. Skouloubris; L. Jelsbak; G. Refrégier; H. Myllykallio (npj Antimicrobials and Resistance)
Abstract Antimicrobial combination therapy is widely used to combat Mycobacterium tuberculosis (Mtb), yet resistance rates continue to rise. Mutator strains, with defects in DNA repair genes, drive resistance in other bacterial infections, but their role in Mtb remains unclear. Here, we study the contribution of single nucleotide polymorphisms (SNPs) in DNA Repair, Replication, and Recombination (3 R) genes to Mtb resistance. Through large-scale bioinformatics analysis of 53,589 whole-genomes, we identified 18 novel SNPs in lineages 2 and 4 linked to genotypic drug resistance in 3 R genes, covering 12.5% of clinical isolates with available genome sequences. Notably, a number of the detected SNPs were positively selected during Mtb evolution. Experimental tests showed that mutM, fpgg2, xthA, and nucS mutants had increased the mutation frequency compared to the wild type. Our findings highlight the role of 3 R gene mutations in resistance, emphasizing the need for surveillance to improve early detection and control strategies.